Research Status of Evolution of Microstructure and Properties of Sn-Based Lead-Free Composite Solder Alloys. (14th December 2020) - Li, Shuai; Wang, Xingxing; Liu, Zhongying; Mao, Feng; Jiu, Yongtao; Luo, Jingyi; Shangguan, Linjian; Jin, Xiangjie; Wu, Gang; Zhang, Shuye; He, Peng; Long, Weimin
Abstract : With the miniaturization of solder joints and deterioration of serving environment, much effort had been taken to improve the properties of Sn-based lead-free solders. And the fabrication of Sn-based lead-free composite solder alloys by the addition of nanoparticles is one of the effective ways to enhance the properties. In this paper, the recent research progress on the Sn-based lead-free composite solder alloys is reviewed by summarizing the relevant results in representative ones of Sn-Ag-Cu (SAC), Sn-Bi, and other multielement lead-free composite solder alloys. Specifically speaking, the effect of the added nanoparticles on the evolution of wettability, microstructure morphology, and mechanical properties of Sn-based lead-free composite solder alloys are summarized. It is hoped that this paper could supply some beneficial suggestions in developing the novel Sn-based lead-free composite solder alloys. Additionally, the existed issues and future development trends in the exploitation of new novel Sn-based lead-free composite solder alloys are proposed.